Infectious diseases as complications following spinal cord injury - John Nolan; Tjokorda Gde Bagus Mahadewa (Neurologico Spinale Medico Chirurgico, 2021)
Background: Infectious complications in spinal cord injury (SCI) patients can increase the mortality and morbidity of the patients. The inability to do daily activity is the main cause of the occurrence of infectious complications. Good understanding and high awareness are needed to notice some infectious complications which are difficult to be diagnosed. Method: This paper is a literature review which was done by reviewing and searching journals with “infectious complication”, “spinal cord injury”, “infection” on the search engines. The authors found 52 articles are suitable to be composed as references for this paper. Outcome: Several infectious complications may occur following the incidence of SCI and have a lot of disadvantages. The causes of these infections are multifactorial. Urinary tract infection, infected pressure ulcer, pneumonia, and some other infectious diseases may appear as complications. Extra care in hygiene and sanitation is needed, besides, high awareness is needed to discover these complications. Conclusion: Monitoring post-SCI complications are complex and difficult. A high level of suspicion should be raised with frequent aseptic actions and procedures. Appropriate management including non-surgical or surgical procedures can be chosen to achieve the best outcomes. Early diagnosis and management are critical for the best treatment results.